Water Holding Capacity (WHC), Protein and Moisture Content on Different Concentration of Ginger (Zingiber Officinale Roscoe) Extract and Soaking Time (Jurnal Ilmu dan Teknologi Hasil Ternak, 2011)
The aims of this research was to study the effect of different concentration of ginger extract and soaking time to produce beef meat on WHC, protein content, and moisture content. This study was carried out factorial type of Randomized Complete Design. Factor 1 was ginger extract (J) : (j1) 0%, (J2) 5%, (J3) 10%, and factor 2 was soaking time (P): 5, 10, and 20 minutes. All treatments was replicated in three times, and if three was significant different, it would be tested using BNT. The research result showed that the higher of ginger extract concentration and the longer soaking time, the higher of WHC, protein content, and moisture content. 10 % ginger extract and 20 minutes gave the best result on WHC, protein content, and moisture content. Key Words : Dendeng, Ginger, Soaking Time, WHC, Protein, Moisture Content